Increased risk of suicide among patients with social anxiety disorder - Han-Ting Wei; Shih-Jen Tsai; Chih-Ming Cheng; Wen-Han Chang; Ya-Mei Bai; Tung-Ping Su; Tzeng-Ji Chen; Mu-Hong Chen (Epidemiology and Psychiatric Sciences)
Abstract Aims Increasing evidence has established a strong association between social anxiety disorder and suicidal behaviours, including suicidal ideation and suicide attempts. However, the association between social anxiety disorder and suicide mortality remains unclear.